Impact of Mobile Telecommunications Traffic on the Development of Postal Traffic - Kljak, Tomislav; Bolarić, Marijan; Binički, Marijan (Promet - Traffic&Transportation, 2012)
The key hypothesis of the paper is the existence of a particular impact occurring between the development of mobile telecommunications traffic and the development of postal traffic. The objective of the paper is to ascertain the strength of the impact as well as the nature (type) of the impact in the case of the state of the art in the Republic of Croatia. Relevant data have been collected regarding the number of postal services realised (letters and parcels), minutes referring to duration of the voice conversations within, from and towards mobile networks as well as the number of text messages (SMSs) sent. The interrelations between the postal traffic and mobile telecommunications traffic have been determined following the multi-regression linear modelling which has been statistically tested after having been determined. KEY WORDS: postal traffic, multi-regression modelling, mobile telecommunications traffic